2020
DOI: 10.1016/j.ijid.2020.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of treatment with nafamostat in elderly patients with COVID-19 pneumonia who need oxygen therapy

Abstract: No effective treatment for COVID-19 has been well established yet. Nafamostat, known as anticoagulant, has potential anti-inflammatory and anti-viral activities against COVID-19. We report three cases of COVID-19 pneumonia who progressed while using antiviral drugs and needed supplementary oxygen therapy, improved after treatment with nafamostat. These preliminary findings show the possibility that Nafamostat can be considered to be used in elderly patients with COVID-19 pneumonia who need oxygen therapy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 6 publications
4
65
1
1
Order By: Relevance
“…Indeed, Jang et al reported three cases of elderly patients with COVID-19 pneumonia who showed sufficient recovery with nafamostat therapy in this journal ( Jang and Rhee, 2020 ). Their successful experience would encourage its future use in COVID-19.…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, Jang et al reported three cases of elderly patients with COVID-19 pneumonia who showed sufficient recovery with nafamostat therapy in this journal ( Jang and Rhee, 2020 ). Their successful experience would encourage its future use in COVID-19.…”
Section: Introductionmentioning
confidence: 88%
“…Nafamostat is reportedly effective against COVID-19 [ 84 , 85 ], but the significance of this agent in combination with heparin is hoped to be verified. Nafamostat administered during ECMO treatment (heparin is required) is inevitably administered in combination with heparin.…”
Section: Three Reasons Nafamostat Is Effective Against Covid-19mentioning
confidence: 99%
“…Baricitinib Inflammatory diseases, rheumatoid Arthritis 90,91 Reducing inflammatory responses, 90,91 having a greater efficiency in combination with RDV and LPV-RTV, 93 having the possibility of creating anemia 95,96 Corticosteroids (CSs) Inflammatory diseases 98 Reducing mortality, 102 having short-term or long-term side effects Anakinra Inflammatory diseases 108 Having good performance, reducing mortality, [110][111][112] Tocilizumab (TCZ) Inflammatory diseases, rheumatoid arthritis 116 Showing significant clinical progress, reducing inflammatory markers, reducing mortality, reducing the risk of invasive mechanical ventilation, improving oxygen delivery in patients, having few side effects [117][118][119][120][121][122][123] Anticoagulants Heparin Coagulation problems 130 Reducing mortality, 129 having side effects including drug resistance and heparin-induced thrombocytopenia (HIT) 130,131 Nafamostat mesylate Coagulation problems 134 Having the ability for in vitro inhibition of SARS-CoV-2 S protein-mediated cell fusion and its infection, [132][133][134] improving clinical conditions in patients in need of supplementary oxygen therapy. 135 Arbidol (ARB)…”
Section: Immune Modulatorsmentioning
confidence: 99%
“…[132][133][134] It has also been reported that the use of this safe drug has improved clinical conditions in COVID-19 patients needing supplementary oxygen therapy. 135…”
Section: Heparinmentioning
confidence: 99%